1976
DOI: 10.1017/s0032247400028680
|View full text |Cite
|
Sign up to set email alerts
|

The management of sledge dogs in the Antarctic

Abstract: The British Antarctic Survey (BAS) has relied on sledge dogs as the main form of transport for field parties since its predecessor, the Falkland Islands Dependencies Survey (FIDS), imported them in 1945, when it created a permanent presence on the continent. Over the years dogs have been used for extensive work over a very wide area. In 1975 BAS changed its policy with respect to work in the southern Antarctic Peninsula. In future seasons scientists will not winter in this area but will be flown to Adelaide Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Whereas archaeological research into dog labor is scarce, several studies tied to different goals provided useful data, especially for sled dogs. One study demonstrated that sled dogs averaging 39 kg (85.98 lb) in body mass and acting as a group could pull as much as 115 kg (253.53 lb) each but required frequent rests (Taylor 1955; cited by Bostelmann 1975). Loads of 45 kg (99.21 lb) per animal (115% of body mass) were found more reasonable (Taylor 1955; cited by Bostelmann 1975), and the most efficient load for rapid-transport sled dogs was only 23 kg (50.71 lb, 58.97% of body mass; US War Department 1994).…”
Section: Domestic Dog Morphology Mobility and Labormentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas archaeological research into dog labor is scarce, several studies tied to different goals provided useful data, especially for sled dogs. One study demonstrated that sled dogs averaging 39 kg (85.98 lb) in body mass and acting as a group could pull as much as 115 kg (253.53 lb) each but required frequent rests (Taylor 1955; cited by Bostelmann 1975). Loads of 45 kg (99.21 lb) per animal (115% of body mass) were found more reasonable (Taylor 1955; cited by Bostelmann 1975), and the most efficient load for rapid-transport sled dogs was only 23 kg (50.71 lb, 58.97% of body mass; US War Department 1994).…”
Section: Domestic Dog Morphology Mobility and Labormentioning
confidence: 99%
“…One study demonstrated that sled dogs averaging 39 kg (85.98 lb) in body mass and acting as a group could pull as much as 115 kg (253.53 lb) each but required frequent rests (Taylor 1955; cited by Bostelmann 1975). Loads of 45 kg (99.21 lb) per animal (115% of body mass) were found more reasonable (Taylor 1955; cited by Bostelmann 1975), and the most efficient load for rapid-transport sled dogs was only 23 kg (50.71 lb, 58.97% of body mass; US War Department 1994). These data indicate sled dogs can move extremely large loads (e.g., 115 kg, 253.53 lb or 294.87% of body mass) but do so in teams and in snowy or icy conditions, which reduce friction.…”
Section: Domestic Dog Morphology Mobility and Labormentioning
confidence: 99%